ABHD6 and MAGL control 2-AG levels in the PAG and allodynia in a CSD-induced periorbital model of headache - Liktor-Busa, Erika; Levine, Aidan A.; Palomino, Seph M.; Singh, Simar; Wahl, Jared; Vanderah, Todd W.; Stella, Nephi; Largent-Milnes, Tally M. (Frontiers in Pain Research, 2023)
The high prevalence and severe symptoms of migraine emphasizes the need to identify underlying molecular mechanisms that can be targeted for therapeutic benefit. Clinical endocannabinoid deficiency posits that reduced endocannabinoid tone may contribute to migraine development and other neuropathic pain conditions. While strategies that increase levels of the endocannabinoid N-arachidonoylethanolamine has been tested, few studies have investigated targeting the levels of the more abundant endocannabinoid, 2-arachidonoylglycerol, as an effective migraine intervention. Cortical spreading depression was induced in female Sprague Dawley rats via KCl (potassium chloride) administration, followed by measures of endocannabinoid levels, enzyme activity, and neuroinflammatory markers. Efficacy of inhibiting 2-arachidonoylglycerol hydrolysis to mitigate periorbital allodynia was then tested using reversal and prevention paradigms. We discovered reduced 2-arachidonoylglycerol levels in the periaqueductal grey associated with increased hydrolysis following headache induction. Pharmacological inhibition of the 2-arachidonoylglycerol hydrolyzing enzymes α/β-hydrolase domain-containing 6 and monoacylglycerol lipase reversed and prevented induced periorbital allodynia in a cannabinoid receptor-dependent manner. Our study unravels a mechanistic link between 2-arachidonoylglycerol hydrolysis activity in the periaqueductal grey in a preclinical rat model of migraine. Thus, 2-arachidonoylglycerol hydrolysis inhibitors represent a potential new therapeutic avenue for the treatment of headache.